Características agronômicas de tipos e cultivares de melão, conduzidos com um e dois frutos por planta, em ambiente protegido - Dalastra, Graciela Maiara (2014)
With the objective to evaluate the quality, yield characteristics and gas exchange of three types and cultivars of melon in greenhouse according to the number of fruits per plant three experiments were carried out simultaneously in the greenhouse sector, belongs to Unioeste Campus Marechal Cândido Rondon - PR, from September 2013 to December 2013. The experimental design was randomized blocks in factorial scheme 3 x 2, with six replications. In the first factor were allocated types of melon (canary melon, net melon and frog skin melon) and the second factor was the condution of plants with different number of fruit (one and two fruits per plant ). Three cultivars of melon were used for the canary melon type (AF 4945, Gold Mine and Goldex), net melon type (Acclain, Louis, and Olimpic Express) and frog skin melon type (Medellin, Grand Prix and Sancho). The characteristics evaluated were fruit mass, transversal and longitudinal diameter of the fruit, transversal and longitudinal diameter of the locule, thickness of endocarp, fruit shape index, locule shape index, soluble solids, pH, titratable acidity, firmness fruit, ratio and was estimated the productivity. Measures of gas exchange (photosynthesis, leaf transpiration, stomatal conductance, internal CO2 concentration) were also performed. From these measurements the efficiency of water use was calculated. For the characteristics evaluated, it can be concluded that among the types of melon, frog skin melon type is the most productive. The highest yield occurred in plants with two fruits per plant. Regardless of the number of fruits and the type of melon total soluble solids was higher than the minimum recommended for marketing. Regarding of cultivars of frog skin melon type no significant differences ocured for most variables assessed leading to recommend the cultivation of three cultivars. Regarding of cultivars of net melon type is recommended to cultivate Louis cultivar, by having larger °Brix and firmness without differ from others in relation to productivity. And for the canary melon type, it is recommended to cultivate Goldex. In relation to gas exchange can be concluded that differences in gas exchange indexes to cultivars of melon frog skin melon no influence on productivity and soluble solids content. For melon cultivars of canary melon and net melon type recommended the Goldex and Louis respectively cultivars. The gas exchange indexes, independent of cultivar showed no significant differences regarding the number of fruits, so it is recommended cultivation with two fruits per plant by being more productive without drastic reductions in soluble solids